Adoption of Laser land leveling in South East Asia - CGIAR Research Program on Rice (2019)
The benefits of laser-guided land leveling has spread significantly across South East Asia. Much of its success is due to the strong public-private partnerships, verification in the partner countries and fostering the adoption through field demonstrations, training of stakeholders and support to local equipment supply chains. First users are machinery contract service providers and final users are farmers. Private contract service providers have remarkably increased. The technology is included in national policies for rice self sufficiency.